Research advance in the taxonomy and ecology of Oncaeidae Giesbrecht, 1893 - Sun, Rouxin; Wang, Yanguo; Wang, Chunguang; Xiang, Peng; Chen, Xiaoyin; Xing, Bingpeng (Frontiers in Marine Science, 2022)
The Oncaeidae is an important family of small copepods in marine ecosystems and is characterized by high diversity and abundance. The family was established by Giesbrecht in the late 19th century. Since then, 115 oncaeid species have been discovered and described. However, Oncaeidae species are small-sized and show considerable morphological similarity. The family includes a great number of sibling species and intraspecific form variants. Consequently, there are large knowledge gaps regarding their taxonomy and diversity, and their importance in marine ecosystems may have been underestimated. In this study, we have charted the progress of oncaeid taxonomy and diversity studies worldwide. We have identified the major challenges faced by the researchers and have described the marine science techniques. We also provide an overview of the distribution and ecology of the family Oncaeidae. Progress has been made toward understanding the distribution, habitat preference, and feeding behavior of oncaeids. The knowledge of oncaeids taxonomy has also been considerably increased by improvements in the research methodology, such as the use of molecular biology techniques and interdisciplinary approaches in tandem with the traditional taxonomic methods.